Search for events with Leptonic jets and missing transverse energy in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; et al. (American Physical Society (APS), 2010)
We present the first search for pair production of isolated jets of charged leptons in association with a large imbalance in transverse energy in pp̄ collisions using 5.8fb⊃-1 of integrated luminosity collected by the D0 detector at the Fermilab Tevatron Collider. No excess is observed above the standard model background, and the result is used to set upper limits on the production cross section of pairs of supersymmetric chargino and neutralino particles as a function of dark-photon mass, where the dark photon is produced in the decay of the lightest supersymmetric particle. © 2010 The American Physical Society.
Keywords: Charged leptons; Fermilab Tevatron collider; Integrated luminosity; Lightest supersymmetric particles; Neutralinos; Pair production; Production cross section; The standard model; Transverse energy; Upper limits; High energy physics; Tellurium compounds; Photons